Gårdsbaserad biogas – samarbeten & kontextens betydelse - Nessvi, Rasmus; Nilsson, Anders (SLU/Dept. of Economics, 2018)
The fact that different countries choose to invest in increased production of renewable energy is a continuous trend. This may be a consequence of rising fossil fuel prices, while technological advances has made this production more profitable than before. The Swedish government has also made efforts to strengthen domestic of these energy sources. Part of this effort is to increase the production of biogas. Currently there are about 280 biogas plants I Sweden, of which about 40 is based on agriculture farms. Researchers argue that collaboration is an important part of a farm-based production of biogas.